MSC and HUVEC co-cultured fillers overcome intractable fistula in a new mouse model - Soichiro Hirasawa; Kentaro Murakami; Masayuki Kano; Satoshi Endo; Takeshi Toyozumi; Yasunori Matsumoto; Ryota Otsuka; Nobufumi Sekino; Tadashi Shiraishi; Takahiro Ryuzaki; Kazuya Kinoshita; Takuma Sasaki; et al. (PLoS ONE, 2025)
Anastomotic leakage can lead to intractable fistulae after gastrointestinal surgery in patients with severe comorbidities. In this study, we aimed to devise new intractable fistula mouse models and evaluate the utility of the fillers containing human mesenchymal stem cells (MSCs) and human umbilical vein endothelial cells (HUVECs). After determining the optimal ratio of MSCs to HUVECs as fillers, we created new intractable fistula mouse models and verified the usefulness of the above-mentioned fillers for these fistulas. As the filler containing a 1:1 ratio of MSC: HUVEC showed the highest expression of FGF2 and VEGF among the organization-forming fillers, we determined that this was the optimal ratio. When this filler was transplanted into irradiated and steroid-treated mice with excisional wounds, the skin defects healed significantly faster in the filler-transplanted group than in the non-transplanted group (P < 0.05). Furthermore, we established a new mouse model of a gastrointestinal fistula by securing the cecum to the abdominal wall and puncturing the skin, abdominal wall, and intestinal wall with an indwelling needle. The fistula remained patent for at least seven days and was intractable. Unlike the adhesive group (group 1) (0/5) and the group implanted with fillers containing MSCs (group 2) (1/5), all fistulas were closed in the group implanted with fillers containing MSCs and HUVECs (group 3) (5/5). This study demonstrated that a treatment strategy using HUVEC is advantageous for treating intractable fistulae connected to the gastrointestinal tract. HUVEC should be included when fillers are used to close fistulas.